Effect of metal oxides on some mechanical properties of clear acrylic specific for artificial eye (Mustansiria Dental Journal, 2019)
Aim: the study was undertaken to assess the effect of various metal oxides on somemechanical properties of acrylic resin.Materials and methods: Two hundred acrylic specimens were constructed in total.There were two tests utilized (transverse and hardness). For each test, there werenine experimental groups according to the type of metal oxides used. Thespecimens without use any of metal oxides were considered as control. Fortransverse test, the specimens were exposed to loads until fracture. For hardnesstest, the specimens were tested; values were obtained. All data were analyzed andcompared using ANOVA and tukey tests.Results: the addition of metal oxides at different concentrations enhanced thetransverse strength of acrylic. Significant differences were statistically foundbetween experimental groups and control group (P0.05) except therewas significant difference between control and 5% TiO2 group (P